Pengaruh Tingkat Pendidikan, umur, jenis kelamin, dan Pengalaman Kerja Terhadap Produktivitas Kerja Di Indonesia - Agilia Febianti (Sahmiyya, 2023)
This study aims to discuss the effect of education level, age, gender and work experience on work productivity. The method used in this study was a literature review originating from journals and books relating to the effect of education level, age, gender and work experience on work productivity. The results of this study that there is low productivity is a waste of the company which will reduce the company's profit. Productivity has several factors that influence it, such as the higher a person's education level, the higher the level of productivity or performance of the workforce. The age level is very influential on labor productivity because it is related to the physical abilities of a worker. Gender is related to the differences in the functions, roles and responsibilities of men and women as a result of the agreement formed by society. The existence of workers who have work experience are expected to get jobs according to their expertise. The longer a person is in a job that is in accordance with his expertise, it is hoped that he will be able to increase his productivity.